Electrical properties of nitric acid and DMSO treated PEDOT:PSS/n‐Si hybrid heterostructures for optoelectronic applications. Issue 32 (13th January 2020) - Anitha, R.; Menon, Sumithra S.; Bhalerao, Gopalkrishna; Siddham, Pradeep; Baskar, K.; Singh, Shubra
ABSTRACT: Organic/inorganic heterostructures are an emerging and interesting field of research for optoelectronics. In this work, an efficient organic/inorganic hybrid heterojunction between PEDOT:PSS and n‐type Silicon has been fabricated for optoelectronic applications. Samples with varying thickness of PEDOT:PSS were prepared by spin coating technique and the electrical conductivity of organic layers was modified using DMSO as additive. Post fabrication, the hybrid heterostructures were treated with HNO3 vapor so as to enhance the conductivity of the organic layer. Surface treatment with HNO3 was found to lower the roughness of the organic layer and enhance the transparency of the layer. I – V characteristics reveal optimized behavior of HNO3 treated PEDOT:PSS layer with a low Ideality factor ( n 3.2) and a barrier height (ΦB ) of 0.8 eV. The findings of the study provide a promising efficient method to enhance the electrical and device properties of PEDOT:PSS/n‐Si heterostructures for optoelectronic applications. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48952. Abstract :